BURNOUT PHENOMENON IN MEDICAL STUDENTS - Resti Rahmadika Akbar; Nurul Afifa; Nabila Az Zahrah (Nusantara Hasana Journal, 2024)
Burnout is a condition characterized by physical and mental fatigue, and increased negative feelings or cynicism, decreased effectiveness in doing something and often assuming that they are incompetent. The academic environment of medical schools can be one of the stressors experienced by some students. If stress occurs for a long time and is not balanced with the right coping strategies, then the student can experience academic burnout. Factors that cause burnout can come from both individuals and situations. Heavy academic burdens cause medical students to be at higher risk of experiencing academic burnout when compared to the general population. Students who experience burnout experience extraordinary fatigue both physically and mentally, causing reluctance to interact with others, difficulty concentrating on studying, loss of motivation, reduced sleep quality and interest in attending lectures and activities and causing a feeling of incompetence which will have a negative impact on students both physically, mentally and academically. The worst possibility that can happen is that medical students choose not to continue their education, take leave, even drop out, even to the point of having thoughts of suicide. So that understanding and handling these various aspects, both from an individual and situational perspective, are expected to help prevent and overcome burnout to improve the welfare of medical students.